THE INFLUENCE OF CUSTOMER REVIEWS AND CONFIDENCE ON PURCHASING DECISIONS IN THE MARKETPLACE WITH CONVENIENCE AS AN INTERVENING VARIABLE IN TOKOPEDIA - Yosie Noverha (Jurnal Scientia, 2023)
This research investigates the influence of customer reviews and trusts on purchasing decisions in the marketplace, with convenience as an intervening variable, especially on the Tokopedia platform in Jakarta. A quantitative research design was adopted with data collection through a structured questionnaire survey. The research population includes Tokopedia consumers in Jakarta who have made purchases within the last three months, with 100 respondents selected through purposive sampling. Data collection was carried out in August 2023 to evaluate research variables, including customer reviews, trust, convenience, and purchasing decisions. Data analysis uses Structural Equation Modeling (SEM) techniques with the help of SmartPLS 3.00 software. The research results show that customer reviews and trust play an important role in shaping consumer purchasing decisions on Tokopedia. Customer reviews provide valuable information and create a bond between buyers and sellers through transparency. Trust, a critical element in online transactions, provides a strong foundation for positive business interactions. However, ease of use was not proven to affect purchasing decisions significantly. A platform's success in building trust and providing comprehensive information from customer reviews is a more significant factor in influencing shopper preferences on Tokopedia